Pathology of pediatric liver tumors, a single center experience from south of Iran - Geramizadeh Bita; Bahador Ali; Foroutan Hamid-Reza; Banani Abbas; Nikeghbalian Saman; Malek-Hosseini (Wolters Kluwer Medknow Publications, 2010)
Background: Pediatric hepatic malignancies are rare, accounting for 1-4% of all solid childhood tumors. The histopathology of childhood hepatic tumors guides the treatment and prognosis, and is the cornerstone for precise diagnosis. Until now, there has been no documented study on pediatric liver tumor cases from this center; in this report, we show our experience about the common types of childhood hepatic tumors during five years (2002-2007) and compare them with other studies. Materials and Methods: During five years (2002-2007), all the hepatic tumors of childhood (under 18 year-old) from the pathology file of Namazi Hospital of Shiraz University of Medical Sciences are recorded. This includes both resected specimens and biopsies. All the slides were reviewed and the pathologic diagnosis was confirmed. Results: We detected 53 liver tumor cases in children (below 18 years of age). Among these tumors, 36 (67.9%) were malignant. Male to female ratio was 1.5 to 1. Hepatoblastoma was the most common liver tumor in this age group accounting for 22 patients (41.5%). The second most common primary tumor was hepatocellular carcinoma (HCC), with five patients. Another malignant tumor was embryonal sarcoma. Benign tumors included adenoma, mesenchymal hamartoma, vascular tumors, focal nodular hyperplasia, and inflammatory pseudo tumor. There were also seven metastatic tumors during these five years. Conclusions: The spectrum of hepatic tumors in children is different from that found in the older age group (adults) and also different in different populations.